Pemanfaatan Taman Kota Bagi Gaya Hidup Olahraga Masyarakat Kota Padang - Jerry Herdiandra; Pudia M Indika; Didin Tohidin (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2019)
The problem in this study was the lack of knowledge about the description of the city park for thelifestyle of the people of Padang. The purpose of this study was to find out the description of thecity park for the lifestyle of the people of Padang. This type of research is descriptive. Thepopulation in this study is the people who exercise in the city of Padang, especially in the greenopen space of Imam Bonjol and Taman Muaro Lasak, Purus Beach, Padang. Sampling is done byincidental sampling technique which is anyone who happens to be found in a certain place, in aparking lot, in the field and so on. The technique used to collect data is a questionnaire with aLikert scale. The data obtained were analyzed by descriptive techniques with percentage terms.Based on the results of the study it was found that: The level of achievement of utilization of cityparks for the lifestyle of the community of Padang City was in the good category, as evidenced bythe percentage value of 72.46%. This means that the utilization of city parks for the lifestyle of thesport of the people of Padang City is good